Correction to: Hospital organizational context and delivery of evidence-based stroke care: a cross-sectional study - Andrew, Nadine E; Middleton, Sandy; Grimley, Rohan; Anderson, Craig S; Donnan, Geoffrey A; Lannin, Natasha A; Stroil-Salama, Enna; Grabsch, Brenda; Kilkenny, Monique F; Squires, Janet E; Cadilhac, Dominique A (Université d'Ottawa | University of Ottawa, 2019)
Following publication of the original article [1], the authors reported an error in one of the authors’ names. In this Correction the incorrect and correct author name are shown. The original article has been corrected.